The Genesis of East Asia, 221 B.C.-A.D. 907 - Holcombe, Charles, 1956- (Honolulu : Association for Asian Studies and University of Hawai'i Press, 2001)
The Genesis of East Asia examines in a comprehensive and novel way the critically formative period when a culturally coherent geopolitical region identifiable as East Asia first took shape.
E pluribus sericum -- Civilizing mission: conceiving East Asia -- Beyond East Asia: global connections -- Nuclear implosion -- Before Vietnam -- The birth of Korea -- Japan: insular East Asia -- Conclusion: sinification and its discontents.
Includes bibliographical references (pages 263-323) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: East Asia -- History; Extrême-Orient -- Histoire; 15.75 history of Asia; HISTORY -- General; HISTORY -- Asia -- General; East Asia; Ostasien; China; Natievorming; 15.75 history of Asia; Geschichte 221 v. Chr.-907.; History